Effects of local curvature and magnetic field on forced convection in a layered partly porous channel with area expansion - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
In this study, local curvature effects of upper wall on the separated flow and heat transfer features are numerically examined for a layered channel which contains porous and nanofluid (CNT-water) layers with sudden area expansion under the magnetic field effects. Finite volume method was used for the numerical simulations and impact of different pertinent parameters such as Reynolds number (between 100 and 400), Hartmann number (between 0 and 20), local curvature of the upper wall (r 1 between 2H and 10H, r(2) between 0 and 2H), porous medium Darcy number (between 10(-4) and 5 x 10(-2)), size of the porous layer (between H and 20H) on the convective heat transfer features are numerically analyzed. A novel multi-domain POD approach was used for estimation of flow variables and heat transfer rate. It was observed that the heat transfer rate is enhanced with higher values of Reynolds number, Hartmann number and Darcy number. The peak value and the average value of Nusselt number increase by about 12.86% and 22.48% with magnetic field effects at Ha = 20 when compared to case without magnetic field.There is slight impact of the porous layer size on the fluid flow and heat transfer. However, impact of the curvature of the upper wall on the convective heat transfer feature is significant. The maximum value of local Nusselt number increases up to 4.76 times and therefore it can be used an excellent tool for convective heat transfer control.
Keywords: Porous layer; CNT-nanofluid; Finite volume method; Local curvature; Backward facing step